A importância da avaliação do assoalho pélvico após a prostatectomia radical e seu impacto na disfunção erétil - Jabur, Fernanda [UNESP] (2014)
Radical prostatectomy is one of the treatment options for prostate cancer being carried out by various techniques, but with very high rate of postoperative erectile dysfunction, worsening the quality of life. The exercises for the pelvic floor may promote recovery of erections after radical prostatectomy. This prospective, randomized clinical trial was performed in 80 patients with clinical diagnosis of localized prostate adenocarcinoma who were randomized into three groups: the control group (n = 26) where patients received no specific treatment, the exposure group (n = 30) where patients were instructed to exercise daily in their homes, and the electrical stimulation group (n = 24), where patients underwent anal electrical stimulation and exercises for the pelvic floor daily in their homes. The groups were compared for age, education, postoperative radiotherapy, pathological staging, Gleason score, comorbidities, and BMI, and the only difference among them was heart disease. When carried out the evolution of the IIEF-5 variable strength and timing of contraction in the muscle of the pelvic floor over the twelve months, none of the variables showed significant p-value related to the interaction, that is, the groups have the same performance. We verified the correlation between the values of the IIEF-5 questionnaire and the force of contraction of the pelvic floor, to every analyzed timing measurement, these measures were not correlated. The results showed that rehabilitation of the pelvic floor did not affect the recovery of erectile function in patients over twelve months following radical prostatectomy